The Significance of Justice in the Psychotherapeutic Treatment of Traumatized People After War and Crises - Kizilhan, Jan Ilhan; Neumann, Johanna (Frontiers in Psychiatry, 2020)
In the aftermath of crimes against humanity, human rights violations, and genocide, the question arises whether and how justice can be restored. A lack of social justice and continuing injustice in post-conflict areas prevent survivors from processing their traumatic experiences. As a consequence, the individuals and often their families, their community and the whole society are changed in a lasting way. The trauma can even be passed on over generations. Yet, if war has a negative impact on health, then, programs that focus on achieving justice, peace, and stability should be able to offset or reduce this negative impact. For this reason, the importance of psychosocial well-being and mental health for the reconstruction of societies is acknowledged. Various political, legal, and social programs, like transitional justice, are being implemented in post-war regions to develop justice. Developing or restoring justice also requires good psychosocial care, like a treatment that supports individuals when coping with injustice and gaining a new sense of justice. Such a psychological treatment can make an important contribution when it comes to building new trust and improving mental health. Ethical standards in coping with trauma and developing or restoring justice in post-conflict regions are indispensable to enable long-term peace. The course for new social justice can be set, through a just health system. Thereby, only programs and legal processes, which try to do justice to the survivors and take their needs into account, are ethically justifiable.